Family background, informal networks and the decision to provide for old age: A siblings approach - Bettina Lamla (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In order to encourage people to take out voluntary private pensions to supplement decreasing statutory provisions Germany introduced the so-called Riester pensions. The complex design of the new product might have created entry barriers into the market helping to explain the slow adaption path in the eligible population until today. Existing empirical evidence has not properly taken into account the search and decision costs related to Riester pensions. I use information on family background in order to account for the predisposed ability to manage relevant information as well as to capture the impact of information sharing within families. I conclude that parental erudition as well as experience in financial matters are determinants of their children's preferences and ability in financial decision making, however, omission does not seem to lead to misleading results on other coefficients. Contemporaneous as well as sequential correlations in Riester ownership between siblings are pronounced. While the former might be due to shared preferences, I take the latter as evidence for information sharing. Positive externalities help to overcome entry barriers in the Riester market by dispersing information. The family as a source of information becomes less important with time as the number of Riester owners in other social circles grows. Once a critical mass has been reached positive spillovers create a social multiplier which should result in dynamic demand for Riester contracts. Indeed official statistics exhibit increasing uptake rates among low income individuals for whom initial entry barriers were comparably high.
Keywords: D83; D91; 330